Interferon-α abrogates the suppressive effect of apoptotic cells on dendritic cells in an in vitro model of systemic lupus erythematosus pathogenesis - Abeler-Dörner, Lucie; Rieger, Cosima C.; Berger, Bartlomiej; Weyd, Heiko; Gräf, Daniela; Pfrang, Sandra; Tarner, Ingo H.; Schwarting, Andreas; Lorenz, Hanns-Martin; Müller-Ladner, Ulf; Krammer, Peter H.; Kuhn, Annegret (The journal of rheumatology, 2013)
Objective. An increased incidence of apoptotic cells and an increased activation of dendritic cells (DC) may be involved in the pathogenesis of systemic lupus erythematosus (SLE). We investigated the characteristics of apoptotic neutrophils and monocyte-derived DC of patients with SLE, their interaction, and the influence of autoantibodies and inflammatory cytokines on this interaction. - Methods. Kinetics of neutrophil apoptosis and DC activation were studied by flow cytometry. To analyze the interaction of apoptotic cells with phagocytes, crossover coculture experiments were performed with DC from patients with SLE and apoptotic Jurkat T cells as well as with apoptotic neutrophils from patients with SLE and the monocytic cell line U937. SLE serum and cytokines were added to this coculture, and activation and suppression of DC were quantified by levels of inflammatory cytokine secretion. - Results. Apoptotic neutrophils and DC from patients with SLE showed no inherent defects compared to healthy controls, and the suppressive nature of their interaction was not affected. Autoantibodies as well as the inflammatory cytokines interleukin 17 (IL-17) and IL-1β had no influence on the interaction in this setup. Interferon (IFN)-α, however, substantially reduced the suppressive effect of apoptotic cells on DC. - Conclusion. The data suggest that aberrant immune reactivity in SLE is not generally due to an intrinsic defect in apoptotic cells, their processing, or their interaction with DC, but likely arises from the milieu in which this interaction takes place. Our study highlights the importance of IFN-α during early stages of SLE and its potential as a therapeutic target.